GENETIC DIVERSITY FOR AGRO-MORPHOLOGICAL AND OIL QUALITY TRAITS IN INDIAN MUSTARD (BRASSICA JUNCEA L. CZERN & COSS) - KUMAR, BINOD; PANDEY , ANIL; KR. SINGH, SANJAY (The Bioscan, 2013)
Identification of diverse parents in any crop species like Indian mustard is the pre-requisite and in any crop improvement programme aimed to obtain the desirable recombinants in segregating generations. Greater contribution of additive genetic component was reflected by main shoot length, siliqua on main raceme, siliqua length, palmitic acid, oleic acid and linolenic acid with pronounced range of variation, high heritability coupled with high genetic advance under selection, which may be exploited in early segregating generations for yield and quality enhancement of Indian mustard. Amongst eight, five mono-genotype and clusters III, IV, I with 18, 12 and 11 genotypes, respectively, maximum divergence exhibiting mono-genotype clusters (VII and VIII) may be utilized through inter varietal hybridization to exploit high degree of genetic diversity between them. Noteworthy is that cluster VII exhibiting high genetic diversity for siliqua length, 1000 seed weight, harvest index and seed yield per plant; cluster II and VII for secondary branches per plant, siliqua on main raceme, 1000 seed weight and biological yield per plant heritability coupled with high heritability and genetic gain under selection, may prove their worth in genetic enhancement of mustard for yield and oil quality.